Um voto de fé : fidelização e clientelismo eleitoral na bancada evangélica paulista - Rudi, Luciana de Matos (Universidade Federal de São Carlos, 2006)
The present work examine, historically, all the Brazilian period republican observing practical of advantages politics that had been present in the sphere politic to analyze the performance of the gospel members of the house legislative of São Paulo. The choice of the members with religious filiation was given in reason of the expressive increase of evangelicals, temples and visibility of the gospels. The objective of the work is to verify where measured the clientelism it is present in the analyzed group and of that forms this practical if differentiates of the definite clientelist relation for specific literature. For in such a way, the Projects of Law had been analyzed presented by the group during two mandates, understood between the years of 1999 and 2006, taking in consideration categories defined for the authoress of the work. The study it demonstrates that, even so the clientelism is practical current between these politicians, it operates in the direction of attainment of recognition for the religious ones as well as, for the on entities to the denominations of which there are members. And, operates not more in the geographic level, or either, of electoral redoubts as the traditional clientelism when benefiting cities or regions as a whole. This is clearly when comparing the result of the clientelist exchange in the form of fidelization of the vote that is, basically, the electoral success.
Keywords: Religião e política; Clientelismo; Evangelismo; Projetos de lei; Eleições; Fidelização; Evangélicos; Clientelism; Gospels; Projects of law; Elections; OUTROS::CIENCIAS SOCIAIS